Europeanising the German energy transition - Severin Fischer; Oliver Geden (Stiftung Wissenschaft und Politik (SWP), 2011)
Germany's so-called »Energiewende« (energy transition) of summer 2011 could be the final episode of a long-running political conflict over the use of nuclear energy. The broad consensus assembled by the German government starts a process that will shut down all the country's nuclear power stations by 2022, while still confirming medium- to long-term targets for renewables and the reduction of greenhouse gas emissions. But the intense energy policy debate has remained largely confined to the national context and neglects economic and political interconnections with the EU level. This blinkered perspective not only endangers the success of the energy transition within Germany, but threatens its role as a globally attractive model for a successful shift to a low-carbon economy. If the German transformation is to succeed it must be backed up with political initiatives at the EU level
Keywords: 320